An Instructional Design For The Teaching Of English At SMP Muhammadiyah 5 Surakarta: A Naturalistic Study In 2013/2014 Academic Year - Kurnia, Cinthya Agustin, Dr. Dwi Haryanti, M.Hum, Prof. Dr. Endang Fauziati, M. Hum (2014)
The goal of the study is to describe an instructional design for the teaching English at SMP Muhammadiyah 5 Surakarta in 2013/2014. The type of study is descriptive qualitative, focus on naturalistic study. The result of this study as follow: (1) learning objective are divided into two; they are general objective and specific objective. (2) The model of syllabus used is notionalfunctional syllabus. (3) The instructional material is divided into three kinds, they are; printed material, audio material, and visual material. (4) Classroom procedure used three patterns, they are 3E (exploration, explanation, and elaboration), 4E (engagement, exploration, explanation, and elaboration), 5E; (engagement, exploration, explanation, elaboration, evaluation). (5) Classroom techniques used, namely: repetition, answering question, role play, previewing, skimming and scanning, prediction, and brainstorming. (6) Teachers' roles are teacher as facilitator, teacher as manager and organizer, teacher as assessor, teacher as prompter, teacher as observer, and teacher as motivator. (7) Students' roles are (a) learners plan their own learning program and this ultimately assumes responsibility for what they do in the classroom, (b) learners monitor and evaluate their own progress, (c) learners are members of a group and learn by interacting with others, (d) learners are as tutor other learners, and (e) learners learn from the teacher, from other students, and from other sources. (8) Media used, namely: (a) picture and images, (b) white board on the market pens, (c) computer, and (d) video. (9) Kinds of evaluations are (a) formative evaluation such as daily test, and (b) summative evaluation such as mid test and final test. The models of evaluation forms are multiple choice, and dialogue completion task.